Chemical Profiling and in vitro Evaluation of the Antioxidant, Anti-Inflammatory, and Anti-Bacterial Effects of Algerian Solanum melongena L. - Kellab, Rabah; Boulkenafet, Fouzi; Amokrane, Serine; Benmakhlouf, Zebida; Bensouici, Chawki; Bounamous, Azeddine; Yahia, Abdelouahab; Lambiase, Simonetta; Al-Meklafi, Fahd Abdo; Wadaan, Mohammed Ahmed (Indian Journal of Pharmaceutical Education and Research, 2025)
Aim Solanum melongena L., commonly known as eggplant, is a low-calorie vegetable with high nutritional value due to its rich fiber, vitamins, minerals, and bioactive compounds, particularly polyphenols, which provide antioxidant properties. This study aimed to investigate the chemical composition and biological activities of methanolic extracts from purple S. melongena fruit. Materials and Methods The chemical and biological properties of the methanolic extract were analyzed using both qualitative and quantitative methods. Bioactive compounds were identified through standard methods and Gas Chromatography-Mass Spectrometry (GC-MS). The antioxidant capacity was assessed using free radical scavenging (DPPH, ABTS) and ferric reducing power assays. The extract’s urease inhibition and anti-inflammatory effects were also tested, and antimicrobial activity was evaluated via the agar diffusion method. Results Qualitative analysis detected phenols, alkaloids, terpenoids, steroids, flavonoids, saponins, and anthraquinones. Total phenolic and flavonoid contents were found to be 81 mg GEA/kg and 75 mg QE/kg, respectively. GC-MS analysis revealed 44 chemical compounds, with quinic acid being the most abundant (>60% peak area). Most identified compounds had not been previously reported in S. melongena L. The methanolic extract displayed moderate antioxidant activity across DPPH, ABTS, reducing power, and phenanthroline assays and showed similar moderate effects in urease inhibition and anti-inflammatory assays. Antibacterial activity was strong against all tested species. Discussion The methanolic extract of S. melongena L. exhibits promising antioxidant, anti-urease, anti-inflammatory, and antibacterial properties. However, further research, including metabolomic studies, is necessary to fully understand the metabolic profile and action mechanisms of the identified compounds.
Keywords: Antioxidant; phenolic; Solanum melongena; Gas Chromatography-Mass Spectrometry